Analysis of Determinants of Child Labour in District Chitral, Khyber Pakhtunkhwa - Haq Nawaz Khan,; Jahangir Alam,; Safdar Hussain, (Dialogue Social Science Review (DSSR), 2025)
The study aims to investigate the prevalence and determinants of child labour in District Chitral, an underdeveloped area of Khyber Pakhtunkhwa, Pakistan, recognized for its high literacy rate and the community's strong commitment to education. The study in hand attempted to identify the factors contributing to child labour and analyzed some theoretical underpinnings to eliminate child labour in the given context. To do this, close ended questionnaires were administered to working children followed by interviews. The targeted population was classified into 05 clusters and a sample of 150 subjects was randomly selected. 100 questionnaires complete from all respects were included for analysis using descriptive statistics. 25 in-depth interviews (20 children and 05 employers) were carried out to obtain insight and substantiate the quantitative data. Findings depict poverty, illiteracy, family size and skill learning intentions as determinants of child labour. The absence of intervention of state and regulatory bodies make vulnerability of working children more severe. Findings are consistent with the previous studies.